An insight into the genetic pathway of adenocarcinoma of the small intestine. Issue 2 (1st February 2002) - Wheeler, J M D; Warren, B F; Mortensen, N J McC; Kim, H C; Biddolph, S C; Elia, G; Beck, N E; Williams, G T; Shepherd, N A; Bateman, A C; Bodmer, W F
Abstract : Background: Although the adenoma to carcinoma pathway in colorectal cancer is well described, the mechanisms of carcinogenesis in the small intestine remain unclear. Aims: The aim of this study was to investigate candidate genes in the genetic pathway of adenocarcinoma of the small intestine. Subjects and methods: A total of 21 non-familial, non-ampullary adenocarcinomas of the small intestine were analysed. DNA was extracted from formalin fixed paraffin wax embedded tissue using standard techniques. The replication error (RER) status was determined by amplification of BAT26. The mutation cluster region (MCR) of the adenomatous polyposis coli (APC) gene was screened using polymerase chain reaction single strand conformational polymorphism and direct sequencing. Immunohistochemistry was performed on formalin fixed paraffin wax embedded tissue using monoclonal antibodies for hMLH1, hMSH2, β-catenin, E-cadherin, and p53. Results: Fourteen male and seven female patients with a median age of 64 years (range 21–85) presented with adenocarcinoma of the duodenum (10), jejunum (7), and ileum (4). One cancer (5%) was found to be RER+, and all tumours stained positive for hMLH1 and hMSH2. No mutations were detected in the MCR of the APC gene. β-Catenin showed increased nuclear expression with loss of membranous staining in 10 cancers (48%). Absent or decreased membrane expression of E-cadherin was found in eight cancers (38%). Strong staining of p53 was found in the nucleus of five cancers (24%). Conclusion: We did not detect mutations in the MCR of the APC gene, and this suggests that adenocarcinoma of the small intestine may follow a different genetic pathway to colorectal cancer. Abnormal expression of E-cadherin and β-catenin was common and reflects an early alternative to APC in this pathway in which mutations may be found in adenocarcinoma of the small intestine.